RANCANG BANGUN SISTEM PAKAR UNTUK DIAGNOSIS PENYAKIT HIPERTENSI DENGAN METODE FORWARD CHAINING - Maria Pantouw; Rinaldi Munir; Junaidy Sanger (Fakultas Teknik Universitas Katolik De La Salle Manado, 2021)
Hypertension is a disease that is often called the silent killer because this disease does not cause long-term symptoms. However, this disease can lead to life-threatening complications. If not detected early and treated on time, it will result in severe complications and even cause death. The authors developed an expert system to diagnose hypertension in this study by identifying disease symptoms and providing solutions. This system uses the forward chaining method in its reasoning and is built using the PHP programming language. Based on testing the various functions of the system that has been carried out, it can be concluded that the diagnosis of hypertension in this expert system has been going well.